Structure of liquid In20Sn80 at high temperature: a XAS study. (October 2020) - Iesari, Fabio; Trapananti, Angela; De Panfilis, Simone; Di Cicco, Andrea
Abstract: X-ray absorption measurements of the liquid metal alloy In20 Sn80 have been carried out between 573 and 1073 K. The temperature evolution of the structure is studied through reverse Monte Carlo simulations, combining EXAFS data and partial pair distribution functions. From the equilibrated configurations we were able to obtain information about bond-angle distributions and local geometries, probed by common neighbor analysis. Our study shows a gradual change of the structure with the temperature in the range considered. Abstract : Highlights: The structure of liquid In20Sn80 between 573 K and 1073 K has been determined by XAS. Short range ordering evolves gradually with temperature. No anomalous change of the structure in the investigated temperature range.